Performance-based reward administration as an antecedent of job satisfaction: a case study of Malaysia’s fire and rescue agencies - Azman Ismail; Mohd Ridwan Abd Razak (School of Social, Development and Environmental Studies, Faculty of Social Science and Humanities, Universiti Kebangsaan Malaysia, 2016)
Performance based reward administration is a crucial aspect of organizational reward system. Recent studies reveal that the ability of administrators to appropriately implement communication, participation and performance appraisal in planning and implementing performance-based reward system may have a significant impact on job satisfaction. Although the nature of this relationship is interesting, the role of performance-based reward administration as an important antecedent has not been adequately explained in organizational reward models. This study was undertaken to examine the correlation between performance-based reward administration and job satisfaction in Malaysia. Primary data were gathered from 168 self-report questionnaires completed by employees of fire and rescue agencies in Peninsular Malaysia. The results of SmartPLS path model analysis showed that performance -based rewards administration was positive and significantly correlated with job satisfaction. Overall, the result demonstrated that the capability of administrators to appropriately implement communication, participation and performance appraisal in managing performance based reward system may lead to greater job satisfaction in the organizations studied. Future studies could do well to delve further into aspects of performancebased rewards in organisations such as organizational and personal characteristics, patterns, direction and magnitude of causal relationships, and behavioural elements of organizational justice .